Color-based motion processing is stronger in infants than in adults. - Dobkins, Karen R.; Anderson, Christina M. (Psychological Science., 2002)
The writers explore the development of the dichotomy in adults' vision between color and motion processing. Using red-green stimulus that isolates color-based input to motion processing, they conduct psychophysical experiments with 2-, 3-, and 4-month-olds and adults. They argue that when performance on the red-green motion stimulus was quantified with respect to performance on a luminance (yellow-black) standard, stronger color-based motion processing was observed among infants than among adults. They conculde that color input to motion areas is greater in early life and that motion areas then specialize to the adultlike state by reweighting or selectively pruning their inputs over the course of development.